Effects of Growth Temperature on Morphological and Structural Properties of ZnO Films - Truong, Vo Doan Thanh; Nguyen, Thi Thanh Truc; Vo, Thanh Lan; Huynh, Hoang Trung; Pham, Thi Kim Hang (Journal of Technical Education Science, 2022)
Zinc oxide (ZnO) is one of the most promising oxide possibilities for use in a number of industries due to its unique properties. Because of its broad direct bandgap (3.37 eV) and strong exciton binding energy (60 meV) at ambient temperature, ZnO not only conducts electricity well but also transmits visible light and emits UV light. Here, we investigated the effect of growth temperature on ZnO thin films by changing the growth temperatures from 400 oC to 450 oC. Radio-frequency (RF) magnetron sputtering was used to create ZnO thin films on Si(100) substrates. The atomic force microscopy (AFM) results show that the root-mean-square (RMS) roughness decreases from 6.1 ± 1.0 nm to 4.8 ± 0.6 nm as the growth temperatures increase. XRD patterns display the enhancement of ZnO’s structure when increasing the growth temperature. Our findings indicate that controlling growth temperature is the critical factor in producing high quality ZnO thin films.